Comparative analysis of morphological characteristics of clam (Marcia opima) in mannar coastal belt, Sri Lanka - Sethukali, A.; Nadeeka Thushari, G. G.; Darshaka Jayasena, D. (International Journal of Fisheries and Aquatic Studies, 2018)
The present study was focused on assessment of morphological variations of clam in Mannar lagoon, Sri Lanka. A total of 150 individual clams (fifty individuals per each site; Naruvilikkulam, Achchankulam and Mutharipputhurai) were collected from June to November 2017 and subjected to Discriminant Function Analysis (DFA) using morphometric parameters to identify intra-specific morphological variation. Length-weight relationship and condition factor were assessed for 3 Clam groups. Average shell length, shell height, length and width of hinge plate, and total weight of clams ranged at 47.30- 52.40, 39.60-43.92, 23.41-26.37, 8.83-10.34 mm and 35.80-51.20 g respectively. Predicted model of DFA derived 99.8% and 0.2% of variances for function 1 and 2 respectively. All 3 Clam groups had negative allometric growth pattern (b= <3). Average condition factor (K) calculated for this species was 0.036 indicating unfavorable factors in living habitats. Basic morphological information of Clams is useful in aquaculture and fisheries sector of Sri Lanka.
Keywords: Coastal bivalves; Morphological variation; Discriminant function analysis; Condition factor; Allometric growth